Case report: Responses to the combination of gemcitabine with sirolimus in two patients with TSC-mutated sarcomas - Nassif, Elise F.; Joseph, Cissimol P.; Lazcano, Rossana; Joseph, Jocelyn T.; Thirasastr, Prapassorn; Lazar, Alexander J.; Somaiah, Neeta (Frontiers in Oncology, 2023)
TSC-mutated sarcomas are rare molecular and histologic types of sarcoma. Due to the presence of their specific oncogenic driver mutation, these sarcomas are particularly sensitive to mTOR inhibitors. Recently, nab-sirolimus, an albumin-bound mTOR inhibitor, was approved by the Food and Drug Administration (FDA) for PEComas, which harbor a TSC mutation, and this drug remains the only FDA-approved systemic treatment for these tumors. We report on two cases of patients with TSC-mutated sarcomas who experienced significant responses to the combination of gemcitabine and sirolimus, after progression on prior gemcitabine-based chemotherapy and single agent mTOR inhibition with nab-sirolimus. Preclinical and clinical data support rationale for a synergistic effect of the combination. This combination may represent a valid therapeutic option after failure of nab-sirolimus in these patients, with no standard-of-care treatment options.